Brexit and Its Impact on Turkey-EU and Turkey-UK Relations - NAS, Cigdem (ANKARA UNIV EUROPEAN UNION RESEARCH CENTRE, 2021)
As 2020 comes to a close, the United Kingdom is leaving behind its membership to the European Union (EU). While negotiations over an agreement that will regulate the relations following the exit from the EU, which is called as Brexit, are ongoing, Turkey is also closely watching the developments. Brexit concerns Turkey from various vantage points. Firstly, the influence of the UK's exit on the EU's internal balances and the development of enlargement and integration processes are of significance regarding Turkey's EU candidacy and membership goal. The withdrawal of a member state such as the UK which supports enlargement policy and favours a looser integration model means that EU's leading member states Federal Germany and France will be in a more decisive position in the EU and shape these policies. Moreover, it may be the case that change and opportunities for cooperation may escalate in Turkey's relations with the UK, with which it already has close economic and political relations. The article aims to analyze the influences and changes brought about by Brexit from the perspective of Turkey-EU and Turkey-UK relations.
Keywords: Brexit; United Kingdom; European Union; EU-Turkey relations; Turkey-UK relations; Area Studies